Identification of Candidate Genes Conferring Cold Tolerance to Rice (Oryza sativa L.) at the Bud-Bursting Stage Using Bulk Segregant Analysis Sequencing and Linkage Mapping - Yang, Luomiao; Lei, Lei; Li, Peng; Wang, Jingguo; Wang, Chao; Yang, Fan; Chen, Jiahui; Liu, HuaLong; Zheng, Hongliang; Xin, Wei; Zou, Detang (Frontiers in Plant Science, 2021)
Low-temperature tolerance during the bud bursting stage is an important characteristic of direct-seeded rice. Identiﬁcation of cold-tolerance quantitative trait loci (QTL) in species that can stably tolerate cold environments is crucial for molecular breeding of rice with such traits. In our study, high-throughput QTL-sequencing analyses were performed in a 460-individual F2:3 mapping population to identify the major QTL genomic regions governing cold tolerance at the bud-bursting stage (CTBB) in rice. A novel major QTL, qCTBB9, that controls seed survival rate under low-temperature conditions of 5 °C/9 day was mapped on the 5.40-Mb interval on chromosome 9. Twenty-eight non-synonymous single nucleotide polymorphism (nSNP) markers were designed for the qCTBB9 region based on re-sequencing data and local QTL mapping conducted using traditional linkage analysis. We mapped qCTBB9 to a 483.87-Kb region containing 58 annotated genes, among which six predicted genes contained 13 nSNP loci. Quantitative reverse transcription-polymerase chain reaction analysis revealed that only Os09g0444200 was strongly induced by cold stress. Haplotype analysis further confirmed that the SNP 1654225-bp in the Os09g0444200 coding region plays a key role in regulating the cold tolerance of rice. These results suggest that Os09g0444200 is a potential candidate for qCTBB9. Our results are of great significance to explore the genetic mechanism of rice CTBB and to improve the cold-tolerance of rice varieties by marker-assisted selection.